Blood Microsampling to Monitor Metabolic Profiles During Physical Exercise - Nix, Cindy; Hemmati, Maryam; Cobraiville, Gaël; Servais, Anne-Catherine; Fillet, Marianne (Frontiers in Molecular Biosciences, 2021)
Monitoring approaches and technical improvements are key factors to improve sportsman’s health, training and recovery after an injury. In this study, a targeted metabolomics approach using microsampling with hemaPEN® was developed to measure changes in blood concentrations of 9 amino acids and 4 organic acids before, during and after exercise. The aim of this research project was to investigate if a reliable monitoring of metabolite levels during sport activity can be achieved collecting one drop of whole blood at different time points. HemaPEN device is an easy-to-use and non-invasive microsampling technique designed to collect four accurate and precise blood volumes simultaneously (10.96 µL). Twenty healthy volunteers between 19 and 30 years of age were included in this study. Physical activity consisted in running as fast as possible 1,600 m after 400 m warm-up. One drop of blood was collected at five time points: before exercise, after 800 m running, after 1600 m, 30 minutes and 60 minutes after finishing the exercise. The influence of physical activity on metabolite levels was evaluated using two ultra-high-performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) methods. Analytical performance criteria such as metabolite stability, method precision, trueness and accuracy, were found to be satisfactory. Expected significant metabolic changes were identified for lactic acid, main TCA cycle intermediates and some amino acids (e.g. creatinine, choline and taurine). This preliminary study performed on a small cohort demonstrated the high interest of using microsampling for fluxomics analysis, not only to collect quickly and easily biological samples during sport but also because it is much easier to store and to process the samples compared to classical plasma/serum samples obtained by venipuncture. The present results open new avenue for fluxomics analysis in the context of health care.